Intraductal papilloma of breast with carcinoma in situ and lymph node tuberculosis: a case report - Zhao, Lu; Wu, Li; Luo, Shuai; Li, Yao; Wang, Jinjing (Frontiers in Oncology, 2025)
BackgroundThe simultaneous occurrence of intraductal papilloma and malignant breast lesions is rare, as is the presence of ductal carcinoma in situ (DCIS) alongside axillary tuberculous lymphadenitis. In DCIS cases, axillary lymphadenopathy should initially raise concerns about metastasis; however, other conditions, such as granulomatous diseases or alternative malignancies, may present with similar clinical features. Given the patient’s extended residence in a tuberculosis-endemic region and history of pulmonary tuberculosis, determining the etiology of axillary lymphadenopathy is imperative. Thus, an accurate pathological diagnosis, exclusion of metastatic breast cancer, and precise staging are essential for effective management.Case presentationA 49-year-old female with a decade-long history of pulmonary tuberculosis presented with a right breast mass, first noticed 10 days prior. Color Doppler ultrasound identified a hypoechoic nodule in the right breast, and breast MRI, both with and without contrast, revealed multiple regions of abnormal enhancement in the right breast, along with enlarged axillary lymph nodes. Tissue biopsy confirmed intraductal papilloma with malignant transformation in some areas (low-grade DCIS). Axillary lymph node biopsy was positive for tuberculosis. The patient underwent right mastectomy, and follow-up after one month showed no recurrence.ConclusionTuberculosis remains prevalent in developing countries, and this patient’s history of pulmonary tuberculosis spans over 10 years. The co-occurrence of breast cancer and axillary tuberculous lymphadenitis is unusual. A prompt and accurate diagnosis of breast cancer is vital, involving preoperative imaging, biopsy, and pathological assessment during and after surgery. Once diagnosed, a treatment plan tailored to the characteristics of carcinoma in situ should be implemented, alongside concurrent treatment for tuberculosis, to improve the patient’s prognosis.